Sensitivity and specificity of cutoff points of resting heart rate from 6,794 brazilian adolescents: A cross-sectional study - Farah, Breno Quintella; Destro Christofaro, Diego Giulliano [UNESP]; Andrade-Lima, Aluísio; Germano-Soares, Antonio Henrique; Tebar, William Rodrigues [UNESP]; De Barros, Mauro Virgílio Gomes; Ritti-Dias, Raphael Mendes (My University, 2021)
Background: Resting heart rate (RHR) may be a useful screening tool for cardiovascular risk. However, RHR cutoff points, an interesting clinical approach, have never been described in young populations. Objective: To establish RHR cutoff points in Brazilian adolescents and to analyze whether cutoff points are associated with cardiovascular risk factors. Methods: The sample was composed of 6,794 adolescents (10 to 19 years old). Blood pressure and RHR were assessed by oscillometric device. Body mass index and waist circumference were also assessed. Receiver operating characteristic curve was adopted to analyze the sensitivity and specificity, and associations of high RHR with cardiovascular risk factors were analyzed by binary logistic regression. A p value < 0.05 was considered statistically significant for all the analyses. Results: Mean RHR values were higher among participants ages 10 to 14 years than 15 to 19 years, for boys (p < 0.001) and girls (< 0.001). The proposed RHR cutoff points for cardiovascular risk factors detection were significant for boys ages 10 to 14 (> 92 bpm) and 15 to 19 years (> 82 bpm), as well as for girls ages 15 to 19 years (> 82 bpm) (p < 0.05 for all), whereas no cutoff point was identified for girls ages 10 to 14 years (p > 0.05). Proposed RHR cutoff points were associated with abdominal obesity, overweight, and high blood pressure in boys in girls. RHR cutoff points were associated with the cluster of cardiovascular risk factors in adolescents ages 15 to 19 years. Conclusion: The proposed RHR cutoff points were associated with cardiovascular risk factors in adolescents.
Keywords: Adiposity; Adolescent; Blood Arterial; Cross-Sectional Studies; Epidemiology; Heart Rate; Obesity; Risk Factors